2014
DOI: 10.1038/cdd.2014.69
|View full text |Cite
|
Sign up to set email alerts
|

Integrated high-throughput analysis identifies Sp1 as a crucial determinant of p53-mediated apoptosis

Abstract: The restoration of p53 tumor suppressor function is a promising therapeutic strategy to combat cancer. However, the biological outcomes of p53 activation, ranging from the promotion of growth arrest to the induction of cell death, are hard to predict, which limits the clinical application of p53-based therapies. In the present study, we performed an integrated analysis of genome-wide short hairpin RNA screen and gene expression data and uncovered a previously unrecognized role of Sp1 as a central modulator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 34 publications
3
63
0
Order By: Relevance
“…Repression of anti-apoptotic/survival genes in addition with induction of pro-apoptotic targets was shown to critically control the apoptotic outcome of RITA-treated cancer cells. 34,[58][59][60] In glioma cells, we found that Nutlin-3a behaved as shown previously for RITA regarding the p53 transcriptional repression activity. 34 However, high expression of α5β1 integrin conferred another anti-apoptotic signaling, which we identified to be in part supported by PEA-15.…”
Section: Discussionsupporting
confidence: 86%
“…Repression of anti-apoptotic/survival genes in addition with induction of pro-apoptotic targets was shown to critically control the apoptotic outcome of RITA-treated cancer cells. 34,[58][59][60] In glioma cells, we found that Nutlin-3a behaved as shown previously for RITA regarding the p53 transcriptional repression activity. 34 However, high expression of α5β1 integrin conferred another anti-apoptotic signaling, which we identified to be in part supported by PEA-15.…”
Section: Discussionsupporting
confidence: 86%
“…For example, cell cycle genes were preferentially enriched for the middle to late phases during the time course, consistent with the finding of enriched cell cycle regulator motifs in the promoters of these genes, e.g., the E2F1, c-MYC, HIF-1a, and MITF genes (82)(83)(84)(85)(86). The middle and late categories were also enriched for stress response genes, which is consistent with the motif enrichments of factors involved in stress responses, such as E2F7, HIF-1a, and SP1 (87)(88)(89)(90). Furthermore, gene promoters of each category were enriched for motifs related to circadian rhythm.…”
Section: Discussionsupporting
confidence: 72%
“…A genome-wide analysis of chromatin occupancy by p53 and a parallel analysis of gene expression have identified Sp1 as one of the p53 modulators that confer specificity to p53-mediated transcriptional response upon induction of tumor cell apoptosis (Nikulenkov, et al, 2012). Although Sp1 could be indispensable for the proapoptotic transcriptional repression by p53, it is not for the induction of pro-apoptotic genes (Li, et al, 2014a).…”
Section: Sp1 Is Involved In Cell Growth and Tumorigenesismentioning
confidence: 99%